Simultaneous Endocardial and Epicardial Delineation of 3D Reentrant Ventricular Tachycardia - Tung, Roderick; Raiman, Michael; Liao, Hongtao; Zhan, Xianzhang; Chung, Fa Po; Nagel, Rich; Hu, Hongde; Jian, Jiang; Shatz, Dalise Y.; Besser, Stephanie A.; Aziz, Zaid A.; Beaser, Andrew D.; et al. (Journal of the American College of Cardiology, 2020)
Mechanisms of scar-related ventricular tachycardia (VT) are largely based on computational and animal models that portray a 2-dimensional view. The authors sought to delineate the human VT circuit with a 3-dimensional perspective from recordings obtained by simultaneous endocardial and epicardial mapping. High-resolution mapping was performed during 97 procedures in 89 patients with structural heart disease. Circuits were characterized by systematic isochronal analysis to estimate the dimensions of the isthmus and extent of the exit region recorded on both myocardial surfaces. A total of 151 VT morphologies were mapped, of which 83 underwent simultaneous endocardial and epicardial mapping; 17% of circuits activated in a 2-dimensional plane, restricted to 1 myocardial surface. Three-dimensional activation patterns with nonuniform transmural propagation were observed in 61% of circuits with only 4% showing transmurally uniform activation, and 18% exhibiting focal activation patterns consistent with mid-myocardial reentry. The dimensions of the central isthmus were 17 mm (12 to 28 mm) × 10 mm (9 to 19 mm) with 55% exhibiting a minimal dimension of <1.5 cm. QRS activation was transmural in 63% and located 43 mm (34 to 52 mm) from the central isthmus. On the basis of 6 proposed definitions for epicardial VT, the prevalence of an epicardial circuit ranged from 21% to 80% in ischemic cardiomyopathy and 28% to 77% in nonischemic cardiomyopathy. A 2D perspective oversimplifies the electrophysiological circuit responsible for reentrant human VT and simultaneous endocardial and epicardial mapping facilitates inferences about mid-myocardial activation. Intricate activation patterns are frequently observed on both myocardial surfaces, and the epicardium is functionally involved in the majority of circuits. Human reentry may exist within isthmus dimensions smaller than 1 cm, whereas QRS activation is often transmural and remote from the critical isthmus target. A 3-dimensional perspective of the VT circuit may enhance the precision of ablative therapy and may support a greater role for adjunctive strategies and technology to address arrhythmogenic tissue harbored in the mid-myocardium and subepicardium. [Display omitted]